Handbook of Pediatric Behavioral Healthcare An Interdisciplinary Collaborative Approach (Springer International Publishing, 2018)
This handbook addresses the delivery of high quality pediatric behavioral healthcare services that are multitiered, evidence-based, and integrated, involving interprofessional collaboration across child serving systems, such as pediatrician offices and schools. The book sets forth a contemporary, leading edge approach that reflects the relationship between biological and psychosocial development and the influence of multiple systems, including the family, community, school, and the healthcare system on child development and functioning. It assists child-focused providers in developing knowledge about the relationship between biological and psychosocial development and between pediatric physical health and behavioral health problems. Chapters cover common chronic illnesses and behavioral conditions and include guidelines for screening, assessment, diagnosis, prevention, and coordinated intervention. Chapters also include representative case studies that help illustrate efficacious, effective service-delivery approaches. The handbook concludes with recommendations for future research and directions for integrated pediatric behavioral healthcare. Topics featured in the Handbook include: Behavioral health aspects of chronic physical health conditions, including asthma, diabetes, chronic pain, traumatic brain injury, and cancer. Physical health implications of behavioral health and educational problems, including ADHD, learning disabilities, substance abuse, and ASD. Coping with chronic illness and medical stress. Patient adherence to medical recommendations and treatments. School reintegration after illness. The Handbook of Pediatric Behavioral Healthcare is a must-have resource for researchers, professors, and graduate students as well as clinicians, therapists, and other practitioners in clinical child and school psychology, primary care medicine, social work, child and adolescent psychiatry, public health, health psychology, pediatric medicine, nursing, behavioral therapy, rehabilitation, and counseling.